HUMAN COURAGE AND DIGNITY IN ERNEST J. GAINS A LESSON BEFORE DYING - Simamora Rosa; Linus Rumapea (English Education Department at FKIP Nommensen University, 2021)
This research is on human courage and dignity in Ernest J. Gainess novel, A Lesson Before Dying. People are able to face threat, pain, danger, or even death in order to maintain their right and dignity relying on courage.This is library research and applies mimetic criticism proposed by Abrams saying that a work of literature is the imitation of the real world. It depicts human being who struggles to maintain and get acknowledgement of their right and dignity to live in respect and worth.The analysis focused on how courage and dignity raise someone who is desperated into brave and thoughtful to face his death. He is desperated because of a false accusision of being a murderer, compared as a hog, and sentenced to death in electric chair. Comparing to a hog makes him lost his courage and self-esteem. He eliminates himself and does not want to speak with others. His godmother disagrees with it and asks a teacher to teach him that he is a human being and should die as a human being too. Then, he is taught by a teacher of moral and obligation to face his death courageously and show that he is a human being who has duty and responsibility. Finally, he is able to sacrifice his death as a symbol of his courage and dignity to himself, his family and community. It is found that the author Ernest J Gains through the novel has vividly portrayed human beings who have courage are able to maintain and get acknowledgement of their right and dignity although they have to face threat, pain, danger, or even death.